Edukasi Tanda Dan Gejala Preeklampsia Serta Pencegahannya Pada Ibu Hamil - Uswatun Insani; Jumrotun Ni’mah; Ani Ratnaningsih (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Preeclampsia is a hypertensive disorder in pregnancy. This situation can be pregnancy emergency if this don’t received proper treatment, which is bring a risk for the mother and her fetus. This risk can be continue in birthing period and the postpartum period. The preeclampsia’s signs likes hypertension and proteinuria is a frequently encountered. Other signs of symptoms include edema (especially on the face and around the eyes and hands), weight gain, nauseous and vomiting, stomach pain spreads to the upper limbs, headaches and visual disturbances (blurred vision), tachypnea and anxiety. In community, Edema in pregnant usually considered common and commonplace, however this is sign of preeclampsia. Health education about getting a pregnancy check-up at the health service needs. This community dedication service aims to increasing the knowledge of pregnant women about the signs, symptoms and prevention of preeclampsia and it is hoped that they can prevent this at the start of pregnancy, so the mother and baby are healthy. The counseling method have be used, the sub topic are the signs, symptoms and prevention of preeclampsia. Counseling participants were pregnant women in the Lebaksiu Kidul area, Tegal Regency.